ANALISIS MANAJEMEN PENDIDIKAN DALAM UPAYA PENINGKATAN PRESTASI BELAJAR PESERTA DIDIK PADA JENJANG MADRASAH ALIYAH - Dendodi, Dendodi; Ernani, Ernani; Ardita, Maya (Universitas Tanjungpura, 2025)
This study aims to analyze educational management in improving student achievement at the Madrasah Aliyah (MA) level. Education plays a crucial role in the development of a nation by producing quality human resources. However, various challenges such as inadequate facilities, low teacher qualifications, and ineffective school management often hinder efforts to improve student achievement. This study employs a qualitative method with a literature review approach and interviews with teachers at MA Asy-Syafi’iyyah Singkawang, West Kalimantan. The main obstacles identified from the research include a lack of technological facilities, low student interest in learning, and limited access to information. Effective educational management strategies encompass relevant curriculum management, the application of varied teaching methods, and teacher collaboration. Additionally, active parental participation in education is also a crucial factor. This study provides practical recommendations for enhancing the quality of teaching and learning outcomes, emphasizing the importance of adaptation and innovation in educational management. Thus, this research offers practical recommendations for educators and educational staff to improve the quality of teaching and learning outcomes through good educational management strategies and adequate support from various stakeholders.